Comparing agendas on preventing FGM/C in Guinea-BIssau, Senegal and Gambia - Carvalho, C.; Falcão, Ricardo (Activism in Africa, 2017)
“Comparing agendas on preventing FGM/C in Guinea-BIssau, Senegal and Gambia” comunicação com Ricardo Falcão, Conference Activism in Africa, ISCTE-IUL 11-13 January